2019
DOI: 10.1038/s41586-019-1118-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport protein 2 reprograms neutrophils in cancer

Abstract: Summary Polymorphonuclear myeloid derived suppressor cells (PMN-MDSC) are pathologically activated neutrophils that are critically important for the regulation of immune responses in cancer. They contribute to the failure of cancer therapies and are associated with poor clinical outcomes. Despite the recent advances in understanding of the PMN-MDSC biology, the mechanisms responsible for pathological activation of neutrophils are not well defined, which limits selective targeting of these cells. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
477
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 463 publications
(518 citation statements)
references
References 38 publications
11
477
5
1
Order By: Relevance
“…HPGD expression is induced by androgen and is up-regulated in the androgen-dependent prostate cancer cell line LNCaP 49 . Because PGE 2 has angiogenic 50 and immunosuppressive functions 51 , higher HPGD expression indicates that the malignant region is depleted of PGE 2 and more amenable to cancer immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…HPGD expression is induced by androgen and is up-regulated in the androgen-dependent prostate cancer cell line LNCaP 49 . Because PGE 2 has angiogenic 50 and immunosuppressive functions 51 , higher HPGD expression indicates that the malignant region is depleted of PGE 2 and more amenable to cancer immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, STAT1 may have opposite effects on MDSCs under different conditions. In addition, a recent study indicated that STAT5, which is stimulated by GM-CSF, upregulates the expression of fatty acid transport protein 2 (FATP2) and exerts suppressive activity through the synthesis of prostaglandin E (PGE) [29].…”
Section: Stat Signaling Pathwaymentioning
confidence: 99%
“…A study of the mechanism showed that T-MDSCs but not splenic MDSCs increase lipid uptake, which reveals that the fatty acid translocase CD36, induced by tumor-derived cytokines (G-CSF and GM-CSF) and targeted by the STAT3 and STAT5 signaling pathways, is relevant to FAO and immunosuppression of T-MDSCs [78]. Furthermore, fatty acid transport protein 2 (FATP2) is a long-chain fatty acid transporter that was reported to be overexpressed in mouse and human PMN-MDSCs but not M-MDSCs, is controlled via GM-CSF and STAT5, and exerts suppressive function by means of arachidonic acid uptake and synthesis of PGE2, which was blocked after FATP2 inhibition [29]. Liver X receptors (LXRs) are vital nuclear hormone receptor family transcription factors that participate in lipid homeostasis in mammals.…”
Section: Lipid Metabolismmentioning
confidence: 99%
See 2 more Smart Citations